Does Religion Influence the Motivations of Future Healthcare Professionals to Volunteer During the COVID-19 Pandemic in Poland? An Exploratory Study - Domaradzki, Jan (Journal of religion and health, 2021)
This study was designed to determine the relation between religion and the motivations of future healthcare professionals to volunteer during the COVID-19 outbreak in Poland. Data were collected from 417 healthcare students via an online questionnaire. The results indicated that although students’ religiosity was not a significant predictor of volunteering during the pandemic, it played a key role in determining their motivations to join the fight against COVID-19. There was a significant positive relationship between students’ religiosity and their eagerness to commit for the sake of the community rather than for personal or egoistic motives.